Multiple Functions of Draxin/Netrin-1 Signaling in the Development of Neural Circuits in the Spinal Cord and the Brain - Ahmed, Giasuddin; Shinmyo, Yohei (Frontiers in Neuroanatomy, 2021)
Axon guidance proteins play key roles in the formation of neural circuits during development. We previously identified an axon guidance cue, named draxin, that has no homology with other axon guidance proteins. Draxin is essential for the development of various neural circuits including the spinal cord commissure, corpus callosum, and thalamocortical projections. Draxin has been shown to not only control axon guidance through netrin-1 receptors, deleted in colorectal cancer (Dcc), and neogenin (Neo1) but also modulate netrin-1-mediated axon guidance and fasciculation. In this review, we summarize the multifaceted functions of draxin and netrin-1 signaling in neural circuit formation in the central nervous system. Furthermore, because recent studies suggest that the distributions and functions of axon guidance cues are highly regulated by glycoproteins such as Dystroglycan and Heparan sulfate proteoglycans, we discuss a possible function of glycoproteins in draxin/netrin-1-mediated axon guidance.